ANALISIS PENGARUH PERENCANAAN SUMBER DAYA MANUSIA, BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT. MEGA WARNA LESTARI MEDAN - Simbolon, Sahat; Margaret, Limelvi (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2021)
This study aims to describe the effect of human resource planning, organizational culture and competence on employee performance at PT. Mega Warna Lestari Medan. The population and the sample in this study is 83 (eighty tree) employees using census technique. Research respondents are employees at PT. Mega Warna Lestari Medan, which are 83 employees. The data research instruments used are questionnaires and documentation. The data analysis technique used are validity test, reliability test, descriptive analysis, multicollinearity test, heteroscedasticity test, normality test, multiple linear analysis, multiple linear reliability coefficient test, partial hypothesis test or t test, simultaneous hypothesis test or F test and the coefficient of determination. The results of descriptive analysis at PT. Mega Warna Lestari for human resource planning is in good category, organizational culture is in very good category, competence is in good category and employee performance is in good category. Based on partial analysis, human resource planning, organizational culture and competence have a positive and significant influence on employee performance at PT. Mega Warna Lestari Medan. Simultaneously, human resource planning, organizational culture and competence have a positive and significant influence on employee performance at PT. Mega Warna Lestari Medan. The contribution of human resource planning, organizational culture and competence to improve employee performance variables amounted to 0,621 or 62,1%, while the remaining 0,389 or 38,9% is influenced by other variables that are not examined by writer in this research, such as working discipline, work motivation and job satisfaction.